Influence of processing conditions on dispersion, electrical and mechanical properties of graphene-filled-silicone rubber composites. (December 2016) - Xu, Hui; Gong, Li-Xiu; Wang, Xu; Zhao, Li; Pei, Yong-Bing; Wang, Gang; Liu, Ya-Jun; Wu, Lian-Bin; Jiang, Jian-Xiong; Tang, Long-Cheng
Abstract: The influence of difference processing conditions on dispersion, electrical and mechanical properties of graphene-filled-silicone rubber (SR) composites was investigated. Transmission optical microscopy, SEM and TEM results revealed that the dispersion levels of graphene sheets in the SR matrix were strongly dependent on the processing conditions. Compared with the mechanical mixing and solution blending methods, the ball-milling procedure produced the best graphene distribution at both macro- and micro- scales. Different from the highest enhancement in electrical conductivity obtained for the solution blending treated composites, the ball-milling treated composites displayed the best improvements in mechanical properties, e.g. ∼113% and ∼62% in tensile strength and 1800 s creep strain at 3.0 wt% graphene, respectively. The morphology and microstructure analysis demonstrated that the ball-milling procedure provided better graphene dispersion and graphene/matrix interface than the other two processing methods, which should be attributed to higher enhancements in the mechanical properties of the resulting SR/graphene composites.